Peningkatan Kreativitas Siswa melalui Pelatihan Pembuatan Batik Ecoprint pada Siswa SD Negeri 2 Pakuan Aji - Astuti, Dwilita; Mariana, Erni; Lestari, Siti; Misrodin, Misrodin; Ariyanto, Bambang; Fitriyani, Indah (Pakis Journal Institute, 2025)
Creativity is one of the important demands in the world of education and life today. The goal is to find out the implementation of ecoprint training in schools, to find out students' creativity in ecoprint training, and to find out students' perceptions after participating in ecoprint training. The methods in this community service are Observation and analysis of problems and needs, Implementation of activities with the school, Core Activities / Ecoprint training, Community Service Results hone students' creativity to make ecoprint batik. The results of this training show that students are able to express their creativity and imagination through area-friendly works. The work has the ability to continue to be enlarged and utilized as an effort to reduce pollution in the surrounding environment.